Characteristics of soil organic carbon and its components under long-term different crop rotation patterns - Xingzhe Zhang; Chunguang Liu; Baicheng Wang; Dehai Xu; Xinrui Shi; Shuai Zhang; Bing Yang; Wenhui Wang; Xianghai Meng (PLoS ONE, 2025)
To clarify the effects of different crop rotation patterns on soil organic carbon content and its components, four treatments were set up: corn continuous cropping, soybean continuous cropping, corn-soybean rotation, and corn-soybean-potato rotation. The relationship between soil organic carbon, active carbon, total nitrogen content, and soil aggregates in the 0–50 cm soil layer was analyzed. The results showed that the corn-soybean-potato rotation treatment significantly improved the stability of soil aggregates, with a water stable aggregate content of>0.25 mm increasing by 23.8% −66.3% compared to continuous cropping. Crop rotation increased the soil structure index of the 0–30 cm soil layer, reaching a maximum of 99.60. Among the activated carbon components, the easily oxidizable carbon content was highest in crop rotation treatment, which increased by 31.8% compared to continuous cropping.The total organic carbon and total nitrogen content in the soil were highest in the corn continuous cropping treatment. The above results indicated that crop rotation can improve soil structure and enhance aggregate stability, but its impact on soil carbon and nitrogen storage is relatively small.